Illocutionary Acts in Disney’s Movie "Jungle Cruise" - Solicha, Imatus; Al-Rosyiidah, Afiifah (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2025)
The purpose of this research is to determine the types of illocutionary acts and the functions of illocutionary acts in the main characters’ utterances from the Disney film "Jungle Cruise." The theories applied to address the study’s objectives are based on Searle (1979) and Leech (1983). This article uses descriptive qualitative method to analyze the data in which the writers play as the primary instrument to provide the data analysis. The utterances made by Frank Wolff and Lily Houghton as the main characters were marked and analyzed. The writers found 235 data of the main characters’ utterances to be examined. There are four types of illocutionary acts found within the utterances, they are assertives with 117 data, directives with 71 data, expressives with 24 data, and commissives with 23 data. There are also four kinds of functions occurred in the movie, they are collaborative with 112 data, competitive with 83 data, convivial with 25 data, and conflictive with 15 data.